Estimulación sensorial y su incidencia en el desarrollo cognitivo de 0 a 2 años en el centro infantil “Mi Pequeño Mundo” en la provincia de Cotopaxi cantón Pujilí parroquia Pujilí en el año lectivo 2014-2015 - Sarzosa Herrera, Stefanía Enriqueta (2015)
The importance of sensory stimulation for cognitive development of children from 0 to 2 years old at the Children's Center "My Little World" was investigated, for which the theoretical framework substantiates categories and dimensions such as integral child development, early stimulation, sensory stimulation, childhood psychology, childhood education, child brain development and cognitive development. The purpose of the issue was providing children in their early years of life the necessary knowledge to develop their full potential, to interact with their surroundings by providing them with skills to social, affective and emotional levels, the sensory stimulation and the cognitive development favors the maturation of the nervous system, causing a series of learning through the senses which are specialized organs able to perceive and convey impressions of the external world, also improving effects on education in the teaching-learning process. The work has a qualitative approach and descriptive type since the characteristics of the research were diagnosed; it was supported by the documentary research by building the theoretical foundation and field research through the observation, application of instruments and validation for analysis of results which permitted to state a proposal as a solution to the problem.